2018
DOI: 10.1007/s11524-018-0251-9
|View full text |Cite
|
Sign up to set email alerts
|

State Firearm Laws and Interstate Transfer of Guns in the USA, 2006–2016

Abstract: In a cross-sectional, panel study, we examined the relationship between state firearm laws and the extent of interstate transfer of guns, as measured by the percentage of crime guns recovered in a state and traced to an in-state source (as opposed to guns recovered in a state and traced to an out-of-state source). We used 2006-2016 data on state firearm laws obtained from a search of selected state statutes and 2006-2016 crime gun trace data from the Bureau of Alcohol, Tobacco, Firearms, and Explosives. We exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 12 publications
(19 reference statements)
0
21
0
1
Order By: Relevance
“…This is consistent with studies examining pairs of states that showed the differential in rearm laws between source and destination states correlated with the movement of rearms between the two states, such that rearms are more likely to move from states with weaker laws to states with stricter laws (9, 13). Similarly, a study of 25 US cities found that cities in states with mandatory registration and licensing systems had a higher proportion of crime-related rearms originating from other states (8), and that states with higher number of rearm laws had a higher percentage of crime-related rearms originating from other states (11).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is consistent with studies examining pairs of states that showed the differential in rearm laws between source and destination states correlated with the movement of rearms between the two states, such that rearms are more likely to move from states with weaker laws to states with stricter laws (9, 13). Similarly, a study of 25 US cities found that cities in states with mandatory registration and licensing systems had a higher proportion of crime-related rearms originating from other states (8), and that states with higher number of rearm laws had a higher percentage of crime-related rearms originating from other states (11).…”
Section: Discussionmentioning
confidence: 95%
“…Following other studies (1,11,15), the independent variable was the rearm law strength score, an unweighted count of state-level rearm laws, with higher scores denoting more laws regulating rearms and fewer laws deregulating rearms (e.g. law providing blanket immunity to rearm manufacturers).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Following other studies (1,11,15), the independent variable was the rearm law strength score, an unweighted count of state-level rearm laws. This variable was obtained from the State Firearm Laws Database, which compiles data on state-level laws in all 50 states since 1991 and codes them into fourteen categories of laws that regulate and deregulate rearms (16).…”
Section: Independent Variablesmentioning
confidence: 99%
“…For example, the implementation of a law limiting handgun purchases in Virginia resulted in a lower proportion of crimerelated rearms recovered in the entire Northeast region that were traced to Virginia (10). States with more stringent rearm laws in general have a higher proportion of crime-related rearms originating from outside the state (8,11), of which a large proportion are from states with weaker rearm laws (12). For pairs of states, increasing rearm law stringency in the source state was associated with reduced movement of rearms between two states, while increasing stringency in the destination state lead to increased movement (9,13).…”
Section: Introductionmentioning
confidence: 99%
“…Licensing laws require prospective handgun purchasers to apply to state or local law enforcement, typically in-person and with fingerprinting of applicants, and undergo a thorough background check before obtaining a license. Licensing laws are associated with reductions in guns diverted for criminal use,4–6 firearm homicide7–9 and firearm suicide 10 11…”
Section: Introductionmentioning
confidence: 99%